Alfa Teste: um recurso educacional digital para diagnóstico de leitura nos anos iniciais do ensino fundamental - Olimpio, Patrícia da Silva (2024)
The literacy process involves several stages, and one of the most crucial is assessing the level of reading and writing skills of the students. The purpose of this research was to develop and implement a mobile Digital Educational Resource (DER) named Alfa Teste, aimed at assisting teachers in the application of diagnostic assessments related to reading skills. The Alfa Teste is a diagnostic assessment tool used by teachers in the early grades of elementary education in the municipality of Aquiraz-CE. The specific objectives of the study were: 1) To identify the functionalities of the DER Alfa Teste based on the usual reading diagnostic process, 2) To evaluate the reading level of students at one of the stages of the diagnostic assessment process in the network through the Alfa Teste, and 3) To validate the use of the DER Alfa Teste with literacy teachers in the municipality of Aquiraz. The Alfa Teste is a mobile application available for Android that utilizes reading diagnostic principles from literacy and reading acquisition theorists within the socio-interactionist perspective, such as Angela Kleiman, Ingedore Koch, and Isabel Solé. The work is also based on evaluative practices and the use of DER in the literacy process. The research had a hybrid nature, using elements of Software Engineering and Human-Computer Interaction (HCI) for the development and validation of the application, and qualitative analysis for the diagnostic assessment process of literacy, as well as the concepts, structure, and functionalities, highlighting the characteristics that differentiate it from similar applications. The results indicate a good acceptance of the Alpha Test by the participating teachers in the research.